New record of monogenean parasite Mymarothecium viatorum (Monogenea; Dactylogyridae) in red-bellied pacu (Piaractus brachypomus) in Indonesia - H. Anshary; S. Sriwulan; A. Amriana (Bulgarian Journal of Veterinary Medicine, 2024)
Red-bellied pacu (Piaractus brachypomus) is a popular exotic fish cultured globally for ornamental and human consumption purposes. In Indonesia, this fish is mainly cultured in Java, including to supply seed to other regions for the ornamental fish trade or aquaculture. Although this exotic fish in widely cultured, information on parasitic infections is negligible. Red-bellied pacus were purchased from a fish farmer and examined for monogenean parasite infection. Monogenean parasites were identified based on morphological and molecular characteristics. Histopathological examinations were performed on gills from heavily infected fish. DNA was extracted from an individual monoge-nean; 18S rRNA PCR product was sequenced and a phylogenetic tree constructed. Morphological and molecular traits identified the monogenean as Mymarothecium viatorum, the first report of the neotropical M. viatorum in this region. The parasite was most likely introduced to Indonesia through the importation of ornamental fish. This parasite had a prevalence of 79% and a mean intensity of 7.1. There was no significant correlation between the parasite abundance and the condition factor of the fish. M. viatorum was more abundant on smaller fish than on larger fish. Gill histopathology showed oedema, severe haemorrhage, and infiltration of inflammatory cells. The occurrence of these parasites could pose a serious threat to the development of red-bellied pacu culture.